Industrial Processing of Algerian Table Olive Cultivars Elaborated as Spanish Style - Sab, Chafiaa; Romero, Concepción; Brenes, Manuel; Montaño, Alfredo; Ouelhadj, Akli; Medina, Eduardo (Frontiers in Microbiology, 2021)
Olives from the Sigoise, Verdale, and Sevillana cultivars were elaborated as Spanish-style table olives by four Algerian factories, and the quality and food safety of the industrial table olives have been studied by the analysis of physicochemical and microbiological parameters. Differences were observed between the treatments carried out by the different factories throughout the manufacturing process, especially during the washing stage, but no significant differences were found between the analyzed samples for the concentration of sugars and polyphenols. The final pH values reached at the end of fermentation ranged between 5.04 and 4.27, and the titratable acidity was above 0.4% for all samples. Lactic and acetic acids were produced in mean concentrations of 0.68% and 0.21% as a result of lactic acid bacteria (LAB) and yeast metabolism, respectively. However, the presence of butyric, isobutyric, and propionic acids was also detected, and was related to the growth of undesirable spoilage microorganisms, responsible for secondary fermentations. The high-throughput sequencing of bacterial DNA suggested the dominance of LAB species belonging to genera Lactiplantibacillus, Leuconostoc, Pediococcus, Oenococcus, or Enterococcus. The Enterobacteriaceae family was detected during the first days of brining and in only one sample after 120 days of fermentation. Other spoilage microorganisms were found, such as Lentilactobacillus buchneri or the Pectinatus and Acetobacter genera, capable of consuming lactic acid and these played an essential role in the onset of spoilage. The Clostridium and Enterobacter genera, producers of butyric and propionic acids, were responsible for the malodorous fermentation present in the industrial samples that were analyzed. The study concluded that the safety of the table olives analyzed was compromised by the presence of undesirable microorganisms and microbial stability was not guaranteed. The elaboration process can be improved by reducing the washing steps and the time should be reduced to avoid the loss of fermentable matter, with the goal of reaching a pH < 4.0 after the fermentation and preventing the possibility of the growth of spoilage microorganisms and foodborne pathogens.